ANALYSIS OF SECTIO CAESAREA DELIVERY AT RSUD SRAGEN, INDONESIA - Wulandari, Yeni; Setiyadi, Noor Alwas; Darnoto, Sri (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2014)
Background:Based on data in Sragen District, 2010 showed that AKI (mother mortality rate) written 69.7/10.000 live births and AKB (baby mortality rate) noticed 6.8/100.000 live births. Caesarean Section method was on of childbirth methods used to decrease AKI and AKB. It was common to be called caesarean Section which giving birth the baby by abdomen incision process. Based on data in private hospital of Sragen District (RSUD Sragen), the caesarean Section method in childbirth was increasing up to 481 until 2011.Method: The research was observational study with case control design. The aims were to explain the medical factors influencing the caesarean Section in that hospital. The population was the mothers with childbirt in hospital. Thus, it was calculated by research providing 100 samples dividing by 50 case samples and 50 control samples.Result: The result showed that there were relationship between CPD (p=0.0001), PEB (p=0.0001), abnormal location of the baby (p=0.0001), twins (p=0.0001) and birth canal problem (p=0.0001) with Sectio Caesarea childbirth action in RSUD Sragen. Keywords: Sectio Caesarea, medical factors